Implementation Of Performance Assessment To Determine Employee Performance - Mutinda Teguh Widayanto; Yuliana; Ismawati; Nurdin Natan (Publisher Cv. Inara, 2021)
This study has a purpose to determine the implementation of performance appraisal to assess employee performance conducted at PT. XYZ Sampling is done by using the census technique, namely taking samples from the total population. The research instrument used a questionnaire. Then test the validity and reliability to test the data requirements. The weighting of the questionnaire uses a Likert scale. The data analysis technique used a correlation test and t-test (hypothesis test).From the research results, the implementation of work performance to assess employee performance is carried out based on the work performance form with an assessment based on a rating scale. Employee performance has been included in the